Arab Sebagai Pilihan Tuhan: Studi Analisis Pemilihan Bahasa al-Qur’an dan Geografis Semenanjung Arab - Abdur Rohman (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2022)
This article aims to reveal why the Qur'an was revealed in Arabia, not in Java or other regions. Some people claim that if the prophet Muhammad descended in Java, the Qur'an would also be in Javanese. The argument, at first glance, has some truth. However, God chose the Arabian Peninsula, where the last revelation was revealed, and the language used to immortalize His revelation was not without reason. This qualitative-library research uses data from books, journals or other written references. God chose Arabia because of several factors: First, geographically, the Arab region was in a strategic position at the midpoint between the Persian and Roman powers and the middle lane, which became the meeting point for caravans from the West, East, South and North. The Kaaba, the center of worship and pilgrimage, supports this strategic location. In addition, another Zam-zam well can still be used for the drinking needs of residents and migrants from ancient times. Secondly, in terms of language selection, Arabic was chosen because it has a natural style that is not possessed by any other language. In addition to language, the diction chosen by the Qur'an is very difficult to match because it provides a pleasing rhythm to the ear. At the end of the verse, the average uses rhyme and rhyme in poetry or rhyme. Some of these advantages are not owned by the language in any book. Thus it is not surprising that the Qur'an is easy to memorize because it has a rhyme like a song. In addition, Arabic has the most vocabulary, so it 'does not need' other languages to explain its language. Third, the translation of the Qur'an cannot be called the Qur'an because the translation will not be able to absorb 100% of the original language's meaning. In addition, the translation of the Qur'an eliminates the miraculous side of the Qur'an itself, including language, diction, rhyme and sentence structure.